Analisa Kesalahan Dalam Berbicara dan Berbahasa pada Diskusi Anak Sekolah Dasar Kelas III dengan Konsep Morfologis di Madrasah Ibtidaiyah Ali Imran Medan - Audina, Fitra; Khairunnisa, Siti; Syajida, Syajida; Atika, Rindi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This article aims to provide an understanding of the proper use of language in class III Madrasah Ibtidaiyah students at Madrasah Ibtidaiyah Ali Imran Medan, where the equivalent of most children uses the wrong language in morphological studies. The research method used is a qualitative descriptive research method by observing elementary school children. The result is that many grade III students of MI use standard language mixed with everyday language so that the pronunciation is not beautiful when applied, students are also used to using regional accents so that when using Indonesian it feels foreign, the purpose of this research is to help students be able to speak according to good and correct terms. Keywords : childrens, Language, Indonesian